The Association Between Perivascular Spaces and Cerebral Blood Flow, Brain Volume, and Cardiovascular Risk - Liu, Sirui; Hou, Bo; You, Hui; Zhang, Yiwei; Zhu, Yicheng; Ma, Chao; Zuo, Zhentao; Feng, Feng (Frontiers in Aging Neuroscience, 2021)
Background: Basal ganglia perivascular spaces (BG-PVS) are associated with cognitive decline and cardiovascular risk factors. There is a lack of studies about the cardiovascular risk burden of BG-PVS and their relation with gray matter volume (GMV) and GM cerebral blood flow (CBF) in the aging brain. Herein, we investigated these two issues in a large sample of cognitively intact older adults. Methods: A total of 734 volunteers were recruited. MRI was performed at 3.0 Tesla using a pseudo-continuous arterial spin labeling (pCASL) sequence and a sagittal isotropic T1-weighted sequence for the CBF and GMV analysis. The images obtained from 406 participants were analyzed to investigate the relationship between the severity of BG-PVS and GMV/CBF. False discovery rate-corrected P-values (PFDR) of < 0.05 were considered significant. The images obtained from 254 participants were used to study the relationship between the severity of BG-PVS and cardiovascular risk burden. BG-PVS were rated using a 5-grade score. The severity of BG-PVS was classified as mild (grade < 3) and severe (grade ≥ 3). Cardiovascular risk burden was assessed by the Framingham General Cardiovascular Risk Score (FGCRS). Results: Severe BG-PVS were associated with significantly smaller GMV and CBF in multiple cortical regions (PFDR < 0.05), and were associated with significantly larger volume in the bilateral caudate nucleus, pallidum, and putamen (PFDR < 0.05). Participants with severe BG-PVS were more likely to have a higher cardiovascular risk burden than the participants with mild BG-PVS (60.71% vs 42.93%; P = 0.02). Conclusion: In cognitively intact older adults, severe BG-PVS are associated with smaller cortical GMV and CBF, larger subcortical GMV, and a higher cardiovascular risk burden.